Singapore’s competitiveness at risk - TAN, Augustine H. H. (Institutional Knowledge at Singapore Management University, 2014)
Singapore’s disappointing second-quarter growth of 2.1 per cent compared with the same period last year has raised concerns about the impact of economic restructuring. When compared with the last quarter, growth even dipped 0.8 per cent. At the same time, productivity performance has been dismal. After rising by 2.2 per cent in 2011, productivity dropped by 1.4 per cent in 2012 and another 0.2 per cent last year.